Implementing Reading Instruction in English Class through Positivism, Phenomenology, and Constructivism as Branches of Philosophy of Science - Wasilatul Munawaroh; Ari Purnawan (FKIP - Universitas Riau, 2026)
This study explores how reading instruction in English classrooms is shaped by three philosophical paradigms, namely positivism, phenomenology, and constructivism, as branches of the philosophy of science. A qualitative multiple case study design was employed, involving six English teachers purposively selected from three A-accredited public senior high schools in Jakarta. The teachers had at least five years of teaching experience and held a bachelor’s degree in English Education. Data were collected through classroom observations, semi-structured interviews, and analysis of teaching documents. Methodological triangulation, member checking, and peer debriefing were used to ensure data credibility. Data were analyzed thematically. The findings revealed three patterns. First, positivist-aligned teachers emphasized measurable outcomes and structured assessments. Second, phenomenological practices fostered personal reflection and multiple interpretations. Third, constructivist instruction encouraged collaboration and critical text-to-world connections. Several teachers blended the three paradigms to respond flexibly to learner needs. The study concludes that making philosophical orientations explicit can strengthen reading pedagogy in English language teaching. The findings can be applied to inform teacher professional development programs, the design of reading curricula in the Merdeka Curriculum, and classroom reading strategies that combine structured skill instruction with reflective and collaborative activities.